An Assessment of the Earthquakes of Ancient Troy, NW Anatolia, Turkey - Kürçer, Akın; Chatzipetros, Alexandros; Tutkun, Salih Zeki; Pavlides, Spyros; Özden, Süha; Syrides, George; Vouvalidis, Kostas; Ulugergerli, Emin; Ateş, Özkan; Ekinci, Yunus Levent (IntechOpen, 2012)
None